A Narrative Review of Myocarditis Following COVID-19 Vaccination - Nasiri, Maziar; Farzad, Marjan; Bidaki, Majid Zare; Hakhamaneshi, Hanieh; Kazemi, Toba; Kooshki, Alireza (Cardiology and Cardiovascular Medicine, 2022)
Myocarditis is a rare but serious consequence of COVID-19 vaccination. This study conducted a narrative review of the research on vaccine-induced myocarditis regarding the type, dose of vaccine, time to present from the vaccine, cardiac history, and patient outcomes. All papers of the year 2021 about the study subject were gathered from PubMed using the following MeSH terms: (?Myocarditis" and "COVID-19 vaccine") with no language restriction. Inclusion criteria were case reports and case series. Our search yielded overall 68 studies. After applying inclusion criteria, only 24 studies were included with the total of 46 patients. Forty-one of 46 (89.1%) of the patients were males. The age range was 14-70 years with a mean age of 28.82±14.65 years. The majority of the myocarditis related COVID-19 vaccine cases (73.9%) were associated with the Pfizer-BioNTech following the second dose of the vaccine. The median time to present from the vaccines was 3 days (range, 1-14 days). 93.5% of cases had no previous cardiac history. 91.3% of myocarditis cases were survived and discharged from the hospital.